DIGITAL TOOLS IN ESSAY WRITING: PERSPECTIVES FROM ENGLISH EDUCATION STUDENTS - Tri Puja; Amrullah (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2025)
This study explores the use of technological writing tools in the essay-writing process, focusing on how these tools help address common challenges such as grammatical errors, plagiarism, translation, and paraphrasing. It investigates the perceptions of sixth-semester students in an English Education Study Program regarding the use of grammar checkers, plagiarism detectors, translation tools, and paraphrasing tools within the context of an essay writing course. A cross-sectional survey design was employed, and data were collected through structured questionnaires. The responses were statistically analysed using descriptive analysis methods in SPSS to identify usage patterns and student attitudes. The results show that students generally have positive views toward the use of technological tools, with most reporting that these tools assist them in overcoming various writing-related difficulties. The findings also indicate that students make use of a variety of tools, depending on their specific needs. The study recommends further research into the pedagogical integration of such tools in academic writing instruction.